Preparation of green cellulose diacetate-based antibacterial wound dressings for wound healing - XIAO, Chuang; ZHANG, Ge; LIANG, Wencheng; WANG, Zhaochuang; LU, Qiaohui; SHI, Weibin; ZHOU, Yan; GUAN, Yong; LANG, Meidong (Frontiers of materials science, 2022)
Managing wounds is a growing universal problem and developing effective wound dressings to staunch bleeding and protect wounds from bacterial infections is an increasingly serious challenge. In this work, a remolding electrospinning nanofiber three-dimensional structure wound dressing (CCP) was prepared with superhydrophilicity, high water absorption and absorbing capacity, excellent hemostatic capacity and antibacterial ability, and biocompatibility to promote wound healing. Polyhexamethylene guanidine hydrochloride (PHMG) was grafted to cellulose diacetate (CDA) wound dressing surface through an amide reaction. A water contact angle analysis demonstrated that CCP wound dressing could be beneficial to promote wound exudate management effectively with rapid absorption of water within 0.2 s. In vitro hemo- and cytocompatibility assay showed that a CCP wound dressing had no significant hemotoxicity or cytoxicity. Specifically, CCP wound dressings could be beneficial to accelerate wound hemostasis and further reduce mortality caused by uncontrolled bleeding. Furthermore, CCP wound dressings have an excellent antibacterial ability, which could be beneficial to inhibit wound inflammatory over-reaction and promote normal wound healing. Combined together, the prepared wound dressing in this research effort is expected to have high-potential in clinical applications.